Asbab al-Nuzul : Pengertian, Macam-macam, Ungkapan, Urgensi dan Kegunaan - Hakmi Hidayat; Arilia Anesia Putri; Risna Eka Safitri; Tharin Nadhira Aditya (CV. ITTC INDONESIA, 2024)
There are many scholars who have different opinions in defining asbab an-Nuzul, including Az-Zarqani, Ash-Shabuni, Shubhi Shaleh and Manna' Khalil Al-Qattan. However, even though the editorial definition above is slightly different, all of them conclude that asbab an-nuzul is the incident or events that provide the background for the revelation of the verses of the Koran, in order to answer, explain and resolve problems that arise from these events. Asbab an-nuzul is historical material that can be used to provide information on the revelation of verses from the Koran and provide context in understanding its commands. Of course, these materials only cover events at the time when the Koran was still revealed (ashr at-tanzil). In terms of the number of reasons and verses revealed, we can divide the asbab an-nuzul into; Ta'addud Al-Asbab Wa Al-Nazil Wahid and Ta'adud an-nazil wa al-asbab wahid. The expressions or editorials used by the companions to show the revelation of the Koran are not always the same. The editorials are broadly grouped into two categories, namely Sarih (clear) and Muhtamilah (still possible or uncertain). Asbab an-nuzul has an important meaning in interpreting the Koran. A person will not achieve good understanding if he does not understand the history of a verse's asbab an-nuzul. Understanding asbab an-nuzul will be very helpful in understanding the context of the revelation of the verse. It is very important to apply the verses to different cases and occasions. The opportunity for mistakes to occur will be greater if you ignore the history of asbab an-nuzul.